Q. 135.0( 1 Vote )

# Evaluate the following integral:

Let us assume

.....….equation 1

By property we know that

Thus

.....equation 2

Adding equation 1 and equation 2

We know

……equation

Let cosx = y

Differentiating both sides

– sinxdx = dy

sinxdx = – dy

for x = 0

cos0 = y

1 = y

For x = π

cosπ = y

– 1 = y

Substituting equation 3 becomes

2I = π[{3(1) – (1)3} – {3( – 1) – ( – 1)3}]/3

2I = π[2 – { – 3 + 1}]/3

2I = π[2 + 2]/3

I = 2π/3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Fundamental Integration Formula59 mins
Interactive Quiz on Integration by Substitution47 mins
Lecture on Integration by parts55 mins
Lecture on some forms of integration54 mins
Lecture on integration by partial fractions62 mins
Interactive Quiz on Integration by Parts56 mins
Integration by Substitution56 mins
Definite Integration | Ready for a quiz?FREE Class
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses